Self‐efficacy, burnout and academic success in nursing students: A counterfactual mediation analysis. (21st March 2022) - Bulfone, Giampiera; Iovino, Paolo; Mazzotta, Rocco; Sebastian, Michael; Macale, Loreana; Sili, Alessandro; Vellone, Ercole; Alvaro, Rosaria
Abstract: Aim: To test the mediating role of burnout in the relationship between self‐efficacy and academic success in nursing students. Design: This was a cross‐sectional secondary analysis of longitudinal research aimed at exploring the academic success of nursing students. Methods: We enrolled a convenience sample of nursing students attending 21 Italian baccalaureate nursing degree programmes. Data were collected from 2014 to the 2018–2019 academic year. We analysed the wave of data collected during the third year of the programme. The measurements were the Academic Nurse Self‐Efficacy scale (ANSEs) and the Scale of Work Burnout (SWEBO). A mediation analysis with a counterfactual approach was performed. Results: The participants ( n = 556) had a median age of 20 years (IQR 19–22) and the majority was female [70.5% (392/556)]. Academic success was reached by 51.97% (289/556) of the students. The findings reveal a significant direct effect of self‐efficacy on academic success and also a significant indirect effect of this relationship via burnout. Conclusion: The mechanism by which self‐efficacy influences academic performance in nursing students is more complex than a simple direct relationship. Universities should consider screening students for variables affecting academic success to decrease academic costs and increase ranking systems classification. Impact: Nurses' professors should be engaged in strategies to promote self‐efficacy. The area of intervention should be structured both during classes and internships, in tandem with the mentor and the clinical nurse.